COMPUTER DEPENDENCE AND SOME METHODS AND WAYS OF AVOIDING IT AS ONE OF THE BASIC TASKS OF MODERN PEDAGOGY - Navasardyan, A. (Main Issues Of Pedagogy And Psychology, 2013)
The article is dedicated to one of the basic problems in pedagogy, i.e. teenager computer dependence. Some ways and methods of avoiding the dependence and helping those, who are already under the influence of computer are represented in the article. The author puts forward some reasons of children computer dependence and the stages of its development in due course. The article suggests a designed test system to find out the dependence and how deep it has gone. It even may help them in psychological testing.